2019
DOI: 10.1200/cci.18.00115
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Lung Cancer Tumor Board Connecting Eight General Hospitals in Japan via a High-Security Communication Line

Abstract: PURPOSEThe complexity of lung cancer treatment is rapidly increasing, necessitating the use of multidisciplinary approaches for improving outcomes. Although it is common for institutions to have their own tumor boards, tumor boards connecting several general hospitals, and therefore allowing for more diverse opinions, are not prevalent.MATERIALS AND METHODSA tumor board connecting eight hospitals was formed to discuss patients for whom formulating a treatment strategy was difficult. Physicians and hospital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This study adds knowledge about health professionals' experiences of key enabling factors and barriers for national, virtual MDTMs for rare cancers, which is essential for future improvements. Few studies today, have reported on implementation of national MDTMs 8,9 and it is well known that a strategy for implementation is essential for the outcome. 17 Damschroder et al (2009) established the theoretical framework, Consolidated Framework for Implementation Research (CFIR) consisting of five synergetic domains by which implementation is accomplished; the intervention, the inner and outer setting, individual characteristics and process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study adds knowledge about health professionals' experiences of key enabling factors and barriers for national, virtual MDTMs for rare cancers, which is essential for future improvements. Few studies today, have reported on implementation of national MDTMs 8,9 and it is well known that a strategy for implementation is essential for the outcome. 17 Damschroder et al (2009) established the theoretical framework, Consolidated Framework for Implementation Research (CFIR) consisting of five synergetic domains by which implementation is accomplished; the intervention, the inner and outer setting, individual characteristics and process.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have reported on implementation of national, virtual MDTMs, which makes the evidence-basis thin. 8,9 Virtual MDTMs have been shown to connect geographically spread experts with benefits that particularly relate to improved coordination of care for patients in rural and remote areas and to treatment recommendations for complex cases and rare diseases. 2,[10][11][12][13][14] The MDTM network also provides possibilities for competence development for participating health professionals.…”
Section: Development Of National Virtual Mdtmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual MDC has been employed in multiple settings including evaluation of lung cancer, 16,17 hepatocellular carcinoma, 18 breast cancer, 19 GI cancer, 19 malignant hematology, 19 general oncology, 20,21 and head and neck 22 . Utilization of virtual MDC has been associated with improved referral coordination, 20 decreased delays in diagnosis and treatment, 16,18,20 higher frequency of MDT evaluation, 18 and reduced patient 18,20 and provider travel burden 16 .…”
Section: Prior Experience With Virtual Tumor Boardsmentioning
confidence: 99%
“…Overall, stage III NSCLC is the situation where interdisciplinary management is of upmost importance. There is some evidence for lung cancer in general (including stage III) that a multidisciplinary team improves various aspects of management and probably survival [111][112][113][114][115]. Specifically stage III is examined in a single centre study.…”
Section: Interdisciplinary Multimodality Treatment Approachmentioning
confidence: 99%